(untitled) (Cadernos de Sociomuseologia, 2017)
This article presents an overview on activities and outcomes of the first years of the Postgraduate Program in Museology of the Federal University of Bahia (2013-2016), highlighting its academic production, institutional networks and its participation in seminars. It also lists Masters Degree thesis defended and in progress along this period. Keywords: Postgraduate, Museology, UFBA